What is the general solution of the differential equation? : # x^2(d^2y)/(dx^2)+xdy/dx+n^2y=0 #

Answer 1

#y = C_1 cos(n log x)+C_2 sin(n log x)#

To find out the general solution for

#x^2 y'' + x y' + n^2 y = 0#

we propose a solution with the structure

#y = c x^lambda#

After substitution we get at

#(lambda^2 + n^2) c x^lambda = 0#

then

#lambda = pm i n# or
#y = c_1 x^(i n) + c_2 x^(-i n)# but
#x = e^log x# and #e^(i alpha) = cos alpha + i sin alpha#

so

#y = c_1 e^(i n log x) +c_2 e^(-i n log x)# and also
#y = C_1 cos(n log x)+C_2 sin(n log x)# is the general solution
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

# y = Acos(nlnx) + Bsin(nlnx)#

If we assume the a corrected equation:

# x^2(d^2y)/(dx^2)+xdy/dx+n^2y=0 # ..... [A]

This is a Euler-Cauchy Equation which is typically solved via a change of variable. Consider the substitution:

# x = e^t => xe^(-t)=1#

Then we have,

#dy/dx = e^(-t)dy/dt#, and, #(d^2y)/(dx^2)=((d^2y)/(dt^2)-dy/dt)e^(-2t)#

Substituting into the initial DE [A] we get:

# x^2((d^2y)/(dt^2)-dy/dt)e^(-2t)+xe^(-t)dy/dt+n^2y=0 #
# :. (d^2y)/(dt^2)-dy/dt+dy/dt+n^2y=0 #
# :. (d^2y)/(dt^2)+n^2y=0 # ..... [B]

This is now a second order linear homogeneous Differentiation Equation with constant coefficients. The standard approach is to look at the Auxiliary Equation, which is the quadratic equation with the coefficients of the derivatives, i.e.

# m^2+n^2 = 0# where #n in RR# is a constant

We can solve this quadratic equation, and we get two complex conjugate roots:

# m=+-ni#

Thus the Homogeneous equation [B] has the solution:

# y = e^(0t)(Acosnt+Bsinnt)# # \ \ = Acosnt+Bsinnt#

Now we initially used a change of variable:

# x = e^t => t=lnx #

So restoring this change of variable we get:

# y = Acos(nlnx) + Bsin(nlnx)#

Which is the General Solution.

From the quoted answer we are told that one solution is:

# cos^(-1)(y/b)=log(x/n)^n #
If we assume that the logarithm base is #e# (ie natural logarithms) then we can write this solution as:
# cos^(-1)(y/b)=log(x/n)^n => cos^(-1)(y/b)=nln(x/n)# # :. y/b=cos(nln(x/n))# # :. y=bcos(nln(x/n))#

Which is inconsistent with the solution of the DE, suggesting the quoted solution is in error.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 3

The general solution of the given differential equation is ( y(x) = c_1 x^n + c_2 x^{-n} ), where ( c_1 ) and ( c_2 ) are arbitrary constants, and ( n ) is a constant determined by the characteristic equation ( m(m-1) + m + n^2 = 0 ).

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7